1997
DOI: 10.1111/j.1600-0528.1997.tb00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tooth loss and dental caries in 60‐, 70‐ and 80‐year‐old Swedish individuals

Abstract: The retention of natural teeth among the elderly is increasing and, in recent studies, dental caries has been identified as the main reason for teeth being extracted. The 5-year incidence of tooth loss and dental caries and the most crucial dental factors for tooth extraction were studied in a random sample of 60-, 70- and 80-year-old inhabitants of Gothenburg. Of the 208 persons examined at baseline, 148 (71%) participated in the follow-up examination: 69, 51 and 28 respectively in the different age groups. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
96
3
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 23 publications
(22 reference statements)
15
96
3
1
Order By: Relevance
“…In this study, the percentage of the edentulous population was 21.2%; 26.7% of women and 16.2% of men were edentulous. Although women have reported a higher prevalence of edentulism in some studies, this difference was not significant in the current study (8,9). On the contrary, there was a statistically significant difference in the edentulousness rates between genders in this study; this has also been reported in several other studies (10,11).…”
Section: Resultscontrasting
confidence: 49%
“…In this study, the percentage of the edentulous population was 21.2%; 26.7% of women and 16.2% of men were edentulous. Although women have reported a higher prevalence of edentulism in some studies, this difference was not significant in the current study (8,9). On the contrary, there was a statistically significant difference in the edentulousness rates between genders in this study; this has also been reported in several other studies (10,11).…”
Section: Resultscontrasting
confidence: 49%
“…Current evidence from epidemiological studies focusing on children, young adults, and adults have shown a shift in caries prevalence from occlusal surfaces at younger ages to approximal surfaces with advancing age (2)(3)(4)(5)(6)(7). Unlike the occlusal and free smooth surfaces, the approximal surfaces cannot be visualized directly due to the presence of neighboring teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Today's elderly carry numerous fillings, crowns, and bridges, all subject to the risk of secondary caries. Studies of the causal factors of tooth extraction have shown that caries is an important reason for the loss of teeth even in the oldest age groups (1). In addition, secondary caries is the main reason why crowns and bridges need to be replaced (2,3).…”
mentioning
confidence: 99%